Internet-based cognitive behavioral therapy positively influences the social representations of tinnitus - Manchaiah, Vinaya; Chundu, Srikanth; Ratinaud, Pierre; Andersson, Gerhard; Beukes, Eldre W. (Frontiers in Audiology and Otology, 2023)
The aim of the current study was to examine changes in social representations of tinnitus as a result of Internet-based cognitive behavioral therapy (ICBT). The study used a pre-post design. A total of 106 individuals with tinnitus (mean age 57.5 years) completed a series of questionnaires before and after undertaking ICBT. A free association task was used to collect data. The data were analyzed using qualitative content analysis and also series of quantitative analyses using the IraMuTeQ software. The most common categories reported by individuals with tinnitus before and after ICBT intervention varied. Examination of valance showed that the negative associations decreased from 81% to 56% and the positive and neutral connotations were increased after the intervention. Examination of the frequency of responses and similarities analysis did not reveal major changes following the intervention. However, the prototypical analysis, which considers both the frequency of categories as well as their ranking, showed that more positive and less negative categories appeared in the central zone and in the first periphery following the ICBT intervention. The study suggests that ICBT reduces the negativity associated with tinnitus and increases positivity. The results are consistent with what is seen in patient-reported outcome measures in clinical trials.